Walking Exercise as an alternative choice in lowering blood pressure in hypertensive patients: Systematic Review - Arum Dwi Ningsih (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2020)
Introduction: Hypertension is a condition, where someone has a blood pressure systole ≥ 140mmHg and a blood pressure diastole ≥ 90nmmHg. Hypertension is a health condition that affects 26% of people worldwide. The World Health Organization (WHO) in the "Global NCD Target Reduce Hight Blood Pressure" explained that an increase in blood pressure caused 9.4 million deaths and a major risk factor for global death . Uncontrolled hypertension results in various kinds of complications, even death in a person. Therefore, complex management of pharmacological and non-pharmacological therapies is needed to improve various organs. Walking exercise is one of the non-pharmacological methods in controlling blood pressure. The purpose of this study is to conduct a systematic review of walking exercise on hypertension patients' blood pressure. Methods: Search for articles through a database: Pro quest, Scopus, Science Direct, and EBSCO. Published between 2010 -2020. The method used in the article search is PICOT frame work. Result: There were 13 journals that were analyzed. The review results from 13 journals show that walking exercise effective in reducing blood pressure in hypertensive patients. Conclusion: Walking exercise that is done routinely can reduce blood pressure systole and diastole in hyperetnsi patients. Walking exercise can be included as one of the independent nursing interventions through health education to control blood pressure in hypertensive patients.